Calcitonin gene related peptide involvement in gut health and models of Parkinson's disease - Templeton, Hayley Nicole, author; Tobet, Stuart A., advisor; Myers, Brent, committee member; Smith, Bret, committee member; Moreno, Julie, committee member; Tjalkens, Ronald, committee member (Colorado State University. Libraries, 2025)
The gut plays a central role in maintaining overall health, serving not only as the site of digestion and nutrient absorption but also as a key player in immune function, microbial interactions, and metabolic regulation. Emerging research has highlighted the gut's influence on various diseases, including inflammatory bowel diseases, autoimmune disorders, and neurodegenerative conditions such as Parkinson's disease. Disruptions in intestinal barrier integrity, often referred to as 'leaky gut', have been linked to these conditions, with increased intestinal permeability allowing potentially harmful immunomodulatory substances to enter the bloodstream, triggering inflammation, cellular immune reactivity, and myriad other potential detrimental pathways. Many available models to study gut health lack the cellular diversity and complexity to investigate mechanisms of intestinal barrier dysfunction and epithelial – neural – immune signaling pathways. We developed a device that can maintain the intestinal barrier of intestinal tissue ex vivo for up three days. This was accomplished through the utilization of a dual-flow microfluidic device that uses two gaskets to create individual fluidic channels where luminal and serosal sides of the intestine are separated. The addition of bacterial collagenase to the luminal chamber of this device resulted in a model for investigating 'leaky gut' in the laboratory with recapitulation of important anatomic arrangements and physiologic conditions seen in the in vivo gut wall. A large proportion of Parkinson's disease patients have impaired intestinal barrier integrity. Gastrointestinal symptoms often precede motor symptoms in Parkinson's disease, indicating early gut involvement. The neuropeptide known as calcitonin gene related peptide (CGRP) is involved in regulating gut motility, inflammation, and nociception, and has been linked to both neurodegeneration and altered gut function in Parkinson's disease. A hallmark pathology of Parkinson's is the accumulation of the protein alpha synuclein, in both the central and peripheral nervous systems. Investigation of CGRP's involvement in gastrointestinal pathology of Parkinson's revealed elevated levels of CGRP in the colon. Treatment with CGRP resulted in increased alpha synuclein within gut neurons, implicating a role of CGRP in enteric alpha synuclein accumulation. Understanding CGRP's multifaceted role in PD may provide a novel pathway for therapeutic intervention aimed at improving both gut and central nervous system health in neurodegenerative diseases.